2019
DOI: 10.1128/jb.00722-18
|View full text |Cite
|
Sign up to set email alerts
|

Extragenic Suppression of Elongation Factor P Gene Mutant Phenotypes in Erwinia amylovora

Abstract: Elongation factor P (EF-P) facilitates the translation of certain peptide motifs, including those with multiple proline residues. EF-P must be posttranslationally modified for full functionality; in enterobacteria, this is accomplished by two enzymes, namely, EpmA and EpmB, which catalyze the β-lysylation of EF-P at a conserved lysine position. Mutations to efp or its modifying enzymes produce pleiotropic phenotypes, including decreases in virulence, swimming motility, and extracellular polysaccharide producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Tn5 mutants used throughout were generated and identified using the EZ-Tn5 Kan-2 kit (Lucigen, Middleton, WI) according to the manufacturer's instructions. Targeted deletions of genes were generated by overlap extension PCR as described previously (66). Potential clones were identified by PCR and confirmed by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Tn5 mutants used throughout were generated and identified using the EZ-Tn5 Kan-2 kit (Lucigen, Middleton, WI) according to the manufacturer's instructions. Targeted deletions of genes were generated by overlap extension PCR as described previously (66). Potential clones were identified by PCR and confirmed by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…37 In some organisms, including the increasingly problematic human pathogen Mycobacterium tuberculosis, EFP is reported to be essential. 21,38 Given the ribosome stall-alleviating role of EFP (inter alia [39][40][41][42][43] ) and since it has been shown that i) EFP binds during most (if not all) elongation cycles 44 (and not just during polyproline-associated stalling events), ii) the Lys34 hydroxyl unit (not necessary for function 17,18,28 ) and the amino group from the ligated -lysine residue form hydrogen bonds with the ribosyl-backbone of the CCA P-site tRNA polynucleotide, while the -lysine carbonyland amine moieties bind to the conserved nucleotide A2439 of the 23S rRNA 31 and iii) the -amino acid modification protrudes close in space to the peptide transfer centre; 29,31 we postulated that if PoxA could decorate EFP with -amino acids other than 2, that it would offer an opportunity to influence eubacterial translation very close to the peptide-forming event either in dramatic or subtle ways, depending on the substrates incorporated into EFP and the downstream phenotypic effects of same.…”
mentioning
confidence: 99%